Aspirin Downregulates PDE4D to Inhibit Malignant Progression of Osteosarcoma through the NF-κB/p65 Pathway - Wang, Jinwu; Zhang, Yan; Li, Zhuolun; Li, Yiqin; Zhou, Peng; Xu, Yao; Chen, Long; Yang, Houzhi; Zhang, Chao; Feng, Jinyan; Wang, Guowen (Current Medicinal Chemistry, 2026)
<span class=
Keywords: NF-κB/p65